Unregistered Marriage Practices and Their Consequences: A Case Study in Pesisir Selatan Regency - Febrianti, Lora; Hidayat, Rahmat (Al Mashaadir : Jurnal Ilmu Syariah, 2024)
This research examines unregistered marriages in Pesisir Selatan Regency, obtaining marriage certificates that can be used. The problem formulation for this research is how marital status is not recorded in Pesisir Selatan Regency. The research questions are: 1. What is the background to the existence of unregistered marriages and the implementation of unregistered marriages? 2. What is the validity of unregistered marriages? 3. What is the validity of marriage books, their use and legal consequences? To answer this question, field research was used using interview and documentation data collection techniques. Next, the data that has been collected is analyzed using qualitative methods to provide an overview of the object under study through the data that has been collected and make generally accepted conclusions. The results of this research are: 1. The factors behind the existence of unregistered marriages in Pesisir Selatan Regency are due to inter-ethnic marriages, the absence of a husband or wife's divorce certificate and the existence of a marriage book as proof of the marriage. The wedding was not recorded as taking place at Katik's house, because Katik was the facilitator and/or the marriage provider. 2. The validity of an unregistered marriage has fulfilled the pillars and conditions of marriage in accordance with Islamic religious law. It turned out that there was one couple who did not fulfill the pillars and requirements for a valid marriage. 3. The marriage certificate obtained was fake. The reason it is said to be fake is because there are differences with the original marriage book, even though the marriage book is fake, it can actually be used to make a child's birth certificate.